Designing an Innovative Assessment of HOTS in the Science Learning for the 21st Century - Ichsan, Ilmi Zajuli; Hasanah, Risky; Ristanto, Rizhal Hendi; Rusdi, Rusdi; Cahapay, Michael Bobias; Widiyawati, Yeni; Rahman, Md. Mehadi (Jurnal Penelitian dan Pembelajaran IPA, 2020)
Science learning in the 21st century should develop the abilities of the students to find solutions to the problems. This task requires a set of skills called Higher Order Thinking Skills (HOTS) and innovative assessment should be designed to gauge the acquisition of these skills. Thus, this study aimed to create an innovative HOTS-based assessment tool in science learning. It entailed a method following the research and development model. It covered the topic of genetics and involved biology experts and junior high school students. The result initially showed that the assessment tool has high content validity. It further revealed that the items have a high-reliability index and they loaded on components based on the three HOTS intended for the test. Thus, this paper concludes that the HOTS-based assessment tool is a good classroom test to gauge the science learning of the students.